Glycerol valorization for the generation of acrylic acid via oxidehydration over nanoporous catalyst: Current status and the way forward - Rasrendra, Carolus B.; Culsum, Neng T.U.; Rafiani, Alissya; Kadja, Grandprix T.M. (Bioresource technology reports, 2023)
Transforming glycerol into valuable compounds is one of the strategies to achieve a sustainable biodiesel manufacturing chain. As the outcome, the present issue is to transform glycerol into a value-added compound intended to enhance the functionality of the biodiesel's by-product while also providing a range of critical chemicals to the industry. There are numerous ways of using glycerol conversion to create value-added compounds, with glycerol oxidehydration being one of the most promising for commercial applications. The glycerol oxidehydration using zeolite ZSM-5 as catalyst support exhibits a yield of acrylic acid of around 32 %. In comparison, MCM-22 demonstrates a 16–56 % yield, and mordenite yields approximately 3 %. The selection of the appropriate catalyst dramatically determines the performance of glycerol valorization into acrylic acid. In this review, we comprehensively discussed nanoporous-based catalysts, including zeolites and silica-based materials, for one-step glycerol oxidation. In addition, we present aspects of thermodynamics, kinetics, and the economic evaluation of oxidation processes. [Display omitted] •Nanoporous catalysts for glycerol oxidehydration are comprehensively addressed.•The performance of catalyst is affected by acid-base properties•Aspects of thermodynamics and kinetics are examined.•Techno-economic considerations are provided.